Activity-Dependent Phosphorylation by CaMKIIδ Alters the Ca2+ Affinity of the Multi-C2-Domain Protein Otoferlin - Meese, Sandra; Cepeda, Andreia P.; Gahlen, Felix; Adams, Christopher M.; Ficner, Ralf; Ricci, Anthony J.; Heller, Stefan; Reisinger, Ellen; Herget, Meike (Frontiers in Synaptic Neuroscience, 2017)
Otoferlin is essential for fast Ca2+-triggered transmitter release from auditory inner hair cells (IHCs), playing key roles in synaptic vesicle release, replenishment and retrieval. Dysfunction of otoferlin results in profound prelingual deafness. Despite its crucial role in cochlear synaptic processes, mechanisms regulating otoferlin activity have not been studied to date. Here, we identified Ca2+/calmodulin dependent serine/threonine kinase II delta (CaMKIId) as an otoferlin binding partner by pull-downs from chicken utricles and reassured interaction by a co-immunoprecipitation with heterologously expressed proteins in HEK cells. We confirmed the expression of CaMKIId in rodent IHCs by immunohistochemistry and real-time PCR. A proximity ligation assay indicates close proximity of the two proteins in rat IHCs, suggesting that otoferlin and CaMKIId interact also in mammalian IHCs. In vitro phosphorylation of otoferlin by CaMKIId revealed ten phosphorylation sites, five of which are located within C2-domains. Exchange of serines/threonines at phosphorylated sites into phosphomimetic aspartates reduces the Ca2+-affinity of the recombinant C2F domain by 10-fold, and increases the Ca2+-affinity of the C2C domain. Concordantly, we show that phosphorylation of otoferlin and/or its interaction partners are enhanced upon hair cell depolarization and blocked by pharmacological CaMKII inhibition. We therefore propose that otoferlin activity is regulated by CaMKIId in IHCs.